Placas cimentícias produzidas com a incorporação de pérolas de poliestireno expandido (EPS) - SILVA, Max Weverton Moreira da (Universidade Federal do Pará, 2021)
The Internal and External Vertical Painel Systems are the parts of the residential building that limit it vertically and delimit its environments, such as facades and walls or internal partitions. The use of seals with lower density than masonry provides a reduction in the mass of this subsystem, reducing the demand for aggregates and binders, in addition to reducing the load on the structure, which allows for optimization of its design. The objective of this work is to verify the viability of the production of cementitious slabs with the incorporation of expanded polystyrene (EPS) beads for application in internal vertical sealing elements. For this, mortars with a 1: 3 line (cement: sand) were produced, with levels of incorporation of expanded polystyrene of 0%, 10%, 20% and 30% in relation to the total volume of materials. Mortars were characterized in the fresh state, through the determination of mass density and consistency index, and in the hardened state, for knowledge of the density properties in the hardened state, resistance to compression and traction, and modulus of elasticity. After knowing the characteristics of the mortars, cementitious slabs were produced, reproducing the same trace in the specimens. The plates were tested for bulk density, water absorption, water permeability and flexural strength. The results of this work demonstrated that the cementitious slabs with the incorporation of up to 20% of EPS present technical characteristics for application in internal vertical sealing systems.